Impact of sex on the utilization of defibrillation-capable cardiac implantable devices and outcome: results from the German device registry - Popescu, Sorin Ștefan; Gasperetti, Alessio; Brachmann, Johannes; Eckardt, Lars; Kuck, Karl-Heinz; Willems, Stephan; Lugenbiel, Patrick; Akın, Ibrahim; Meyer, Christian; Schmidtke, Claudia; Schneider, Steffen; Hochadel, Matthias; et al. (Clinical research in cardiology, 2025)
Implantable cardioverter defibrillators (ICDs) and cardiac resynchronization therapy with defibrillation-function (CRT-D) are widely used in patients with life-threatening arrhythmias or heart failure. We aim to investigate the impact of sex-specific differences on defibrillation-capable cardiac devices’ implantation and outcomes.
Gesehen am 12.01.2026